Content Analysis of English Textbook for 11th Grade of Senior High School on HOTS Criteria - Chintara Mentari Putri; Atti Herawati; Mursidah Rahmah (FKIP UNIVERSITAS PAKUAN, 2021)
The newest curriculum or well known as national curriculum has four goals in education of Indonesia. One of them is Higher Order Thinking Skills which means the output of teaching and learning process is required to have higher level of thinking. Thus, the Ministry of Education provides textbook for all level of schools; one of them is for Senior High School. This research aimed to investigate if HOTS is accommodated in English textbook provided by the Ministry of Education; focuses on the content of the textbook, in terms of questions and instructions provided and in relation to HOTS criteria which covers C4 (analyze), C5 (evaluate), and C6 (create). This research applied a qualitative method and used documentation and interview as the instruments. There are four respondents consisting of three English teachers from different schools, and one evaluation expert. The finding shows that HOTS have already been accommodated in English textbook. There are 116 of 211 HOTS questions with frequency 55%, 74 of 252 HOTS instructions with frequency 30%, and factual knowledge as the most dominant knowledge dimension in questions which have 90 of 211 with frequency 43%, and conceptual knowledge as the most dominant knowledge dimension in instructions which have 81 of 252 with frequency 32%. All questions and instructions provided are more about recalling information, guidelines or studies of concepts, describing a factual information and explaining the answer.